Issues of Strategic Legal Regulation of the Implementation of Digital Technologies in Transport - V. N. Voronin (Сибирское юридическое обозрение, 2021)
Despite the awareness of the importance of digital transformation of highways as the basis for life safety, social and economic development of the country, the issues of technical, legal and financial regulation of the digitalization of the transport complex at the federal and regional levels, a detailed assessment of the impact of digital technologies in transport on social and economic processes in modern Russian society. In the Russian doctrine in recent years, research has been carried out in general on the formation and development of the digital economy in Russia, in which intelligent transport systems are mentioned pointwise and only in general terms without their comprehensive analysis. Based on the assessment of the current state and trends in the development of info-communication transport infrastructure in Russia, foreign experience, potential problems of the implementation of digital technologies in transport in the socioeconomic and legal dimension were identified, specific proposals were formulated on the legal and financial regulation of issues and minimization of the risks of liability for harm in conditions development of information transport systems. The role of the programs “Digital Economy of the Russian Federation” and “Safe and High-Quality Roads” in the development of intelligent transport systems has been analyzed, and as a result, promising areas for the use of unmanned vehicles to improve the quality of life of people, develop entrepreneurship, high-tech industries, and increase the investment attractiveness of Russia have been identified. and strengthening its position in the international arena. The study used the following methodological principles: objectivity; determinism; historicism; integrity; consistency; structure; functionality; hierarchy; pluralism of explanation and understanding of law; comparative studies. The study uses private methods: legal analytics, legislative techniques, legal comparative studies, expert assessments. As the main results of the study, the features of the legal regulation of new and promising relations arising in the digital economy have been identified. This is a strategic legal planning and legal experiment. Taking into account this conclusion, a system of prerequisites for the development of intelligent transport systems was formulated based on the analysis of national programs. The system of prerequisites includes three levels: technological prerequisites, infrastructural and regulatory.